A formal behavioral model of firm boundaries: Why does authority relation mitigate ex post adaptation problems? - Yusuke Mori (Osaka University, Institute of Social and Economic Research (ISER), 2013)
We explore why authority within firms helps trading parties immediately settle ex post adaptation problems despite the possibility of a subordinate's disobedience to the orders of his boss. By employing three crucial behavioral assumptions (reference-dependent preference, self-serving bias, and shading), we point out that the choice of governance structure affects trading parties' expectations about outcome of ex post adaptations and show that a subordinate is likely to obey orders of his boss because he is expected to do so. Nevertheless, our study also points out that such a positive aspect of authority comes with subordinate's psychological disutility.
Additional information: The 15th ISER-Moriguchi Prize (2012) Awarded Paper.
Keywords: D23; L22; 330; reference-dependent preference; self-serving bias; contracts as reference points; transaction cost; ex post adaptation; Führungskräfte; Führungspersönlichkeit; Internationaler Markteintritt; Transaktionskosten; Verhaltensökonomik